On Aethina Erichson of Northeast India (Coleoptera: Nitidulidae: Nitidulinae) - Dasgupta, Jhikmik; Pal, Tarun Kumar (Zootaxa, 2022)
Four species of Aethina [Aethina (Aethina) vicina Grouvelle, 1894, Aethina (Idaethina) orientalis (Nietner, 1856), Aethina (Idaethina) subrugosa (Grouvelle, 1894b) and Aethina (Circopes) subquadrata (Motschulsky, 1858)] have been newly recorded from northeast Indian states. Hitherto, three species, viz., Aethina (Aethina) argus Grouvelle, 1890, Aethina (Aethina) cyaneipennis Grouvelle, 1903 and Aethina (Aethina) inconspicua Nakane, 1967 were known from Northeast India. The specific status of Aethina (Aethina) nigrocastanea Grouvelle, 1903 has been reestablished. Altogether eight species of Aethina are treated in this paper. The paper incorporates redescriptions of the genus, and species of Aethina from Northeast India with a key to these species.